BIM-Based method for the verification of building code compliance - Villaschi, Fernanda Schmitd (2022)
Urban planning is a valuable tool for growth control and city development, both to maintain the local urban identity and provide life quality for inhabitants. To regulate it, local governments have defined standards for a proper city’s growth through municipal and detailed urban plans. Such instruments identify a set of rules which constructions and buildings must fulfil for a careful and smooth integration within the urban areas. New projects are required to comply with such rules, and designers must adapt and guarantee that their projects fulfil all the local urban requirements. However, the verification process of construction projects is still a manual procedure and often a time-consuming process, with high possibilities for inaccurate measures. Thus, this paper aims to streamline the verification procedure of construction projects’ code compliance to enhance project design efficiency and save designers time. To do so, the Building Information Modelling (BIM) method will be used through the Dynamo programming software. By creating a Dynamo routine to check the building code and urban plan compliance from Brazilian municipalities, specific BIM models will be automatically analysed to detect and evaluate if it is according to local urban legislation. Results have provided a real-time decision support tool, where designers can assess if their buildings are complying with local urban codes at any time of the design stage, making it easy to innovate and integrate innovative design options, as well as to precisely communicate their buildings’ code compliance. Such a method can also support municipality authorities to verify project compliance, reducing assessment and calculation errors, as well as the required time and bureaucracy for project appraisal.